2010
DOI: 10.1111/j.1464-410x.2010.09369.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic arterial pressure on erectile dysfunction in the initial stages of chronic arterial insufficiency

Abstract: Study Type – Prognosis (case series)
Level of Evidence 4 OBJECTIVE To report the effect of systemic arterial pressure on erectile dysfunction (ED) in patients in the initial stages of peripheral arterial disease. PATIENTS AND METHODS All patients with a diagnosis of ED in the urology outpatient clinic of the Medicine School in São José do Rio Preto, Brazil were evaluated in a cross‐sectional, quantitative study. The patients were assessed using the International Index of Erectile Function, the ankle‐brachial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…ED impacts over 30 million men in North America between the ages of 40 and 70, and significantly affects the quality of life of men and their partners ISSM 2010 Jean Francois Ginestie Prize [7,8]. Recent studies have suggested that nearly 70% of hypertensive males have some degree of ED and hypertension is one of the most common co-morbidities [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…ED impacts over 30 million men in North America between the ages of 40 and 70, and significantly affects the quality of life of men and their partners ISSM 2010 Jean Francois Ginestie Prize [7,8]. Recent studies have suggested that nearly 70% of hypertensive males have some degree of ED and hypertension is one of the most common co-morbidities [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it worsens ED as a result of chronic arterial insufficiency due to the progression of atherosclerosis; on the other hand, it overcomes the obstruction of penile artery stenosis in the initial stages of the disease by directly interfering with pulse pressure. 19 Our findings suggest that decreased cGMP concentration may contribute to ED in the penile tissue of the 2K-1C hypertensive rats after propranolol treatment.…”
Section: Increased Expression Of Igfbpmentioning
confidence: 57%
“…18 Hypertension might protect against ED in the initial stages of chronic arterial insufficiency. 19 However, later on, hypertension has contradictory effects on ED. On the one hand, it worsens ED as a result of chronic arterial insufficiency due to the progression of atherosclerosis; on the other hand, it overcomes the obstruction of penile artery stenosis in the initial stages of the disease by directly interfering with pulse pressure.…”
Section: Increased Expression Of Igfbpmentioning
confidence: 99%
“…Systemic arterial hypertension in the initial stages of peripheral arterial disease might protect against ED, but peripheral arterial disease constitutes an aggravating factor for ED, and thus hypertension might exert a paradoxical effect in this stage of the disease. 6 What is proposed here is that based on the results of assessments, blood vessels appear in some individuals to age and produce "chronic arterial insufficiency" leading to ED. The overall clinical picture suggested that blood pressure rises as a compensatory adjustment perhaps to maintain sexual function.…”
Section: Hypertension-paradoxically Beneficial In Erectile Dysfunction?mentioning
confidence: 99%